Dos Resistant Cloud Based Secure Authentication Protocol (International Journal of Engineering and Computer Science, 2015)
cloud computing has become crucial in todays’ technical environment The identity verification s the man functionality in these cloud computing services. But as on today these identity protection gateways are very inclined from attacks by denial of service.  Numerous authentication protocols are available that are very strong in protecting identities in traditional networked applications.  But these protocols suffer with DOS attacks when we us them in cloud computing applications.  This failure is due to the heavy utilization of cloud resource and lot of verification process involved in these services.  In this paper authors propose a new authentication protocol which overcomes with internal and external denial service attacks. The proposed solution involves multilevel authentication schemes. The technique finds out the legitimate user’s requests and allow them at the front of the processing queue.